INVESTIGATING THE EFFECTS OF PROCESS PARAMETERS ON WRINKLING, FRACTURE AND THINNING OF ALUMINIUM ALLOY 3004-H19 CUPS IN THE DEEP DRAWING PROCESS - P.A.O. ADEGBUYI; K.A. ADEDEJI; R.O OLA-GBADAMOSI (Fiabilitate şi Durabilitate)
The 3004 aluminium alloy is widely used in the container, packaging, and automobile industry. It is the aim of every manufacturing industry to minimize production cost thus the minimization of the deep drawing process parameter dependent defects is essential to the rendering the process profitable. This paper presents a 3D explicit deep drawing finite element analysis (FEA) executed with explicit dynamics module in ANSYSR15 workbench. The effect of blank holding force, punch-die radial clearance, punch-nose and die-shoulder radius was investigated using five different blank holder types(0,7.5,15,25,40)KN, different radial clearance types(3.00,3.15,3.30,3.45,3.60)mm ,and four different types of punch-nose/die shoulder radius(6,8,10,12)mm. A blank of 100mm diameter and 3mm thickness was used in the model. The shear stress, thickness distribution and physical appearance of cups were used to determine the wrinkling, fracture and thinning effect of the varying process parameters. The punch, blank holder and blank was modelled with the ANSYS geometry modeller while the different die geometry was imported from SOLIDWORKS 2017 CAD software. The effect are discussed and from the simulation studies the optimum blank holding force, punch-die radial clearance and punch-nose/Die shoulder radius was 15KN, 3.45mm and 12mm respectively which produced a maximum thinning of 6.33% at the punch corner.